Involvement of Visual Mismatch Negativity in Access Processing to Visual Awareness - Kurita, Yuki; Urakawa, Tomokazu; Araki, Osamu (Frontiers in Human Neuroscience, 2021)
Psychophysiological studies with electroencephalography, focusing on the dynamical aspect of neural correlate of consciousness, reported that visual awareness negativity and P3 enhancement are observed at a latency, 200–300 ms after the visual stimulus onset, when the visual stimulus is consciously perceived. However, access processing to visual awareness (APVA) immediately before conscious perception still remains at the earlier stage of visual sensory processing, though there is little known regarding this subject. The present study hypothesized that visual mismatch negativity (vMMN), which reflects automatic change detection at a latency of 130–250 ms, might be involved in the APVA. In a previous study, vMMN was reported to be evoked by the deviant stimulus that is not consciously perceived in binocular rivalry. To clarify whether the visual change detection affects APVA, we conducted a modified experiment of oddball paradigm on binocular rivalry. The results showed a significant correlation between enhancement of vMMN amplitude and facilitation of perceptual alternation when the unconscious deviant was presented. This implies that vMMN is relevant to the APVA, which is a novel role of vMMN. In early visual processing, the attentional mechanism associated with vMMN is suggested to play an important role in unconscious neural processing at an earlier stage of visual awareness.